(untitled) (Fiep Bulletin - online, 2014)
Regular physical activity and a nutritionally balanced diet are recommended as a cornerstone of a healthy and high quality life. Since adherence to an exercise programme on a regular base is often problematic, a new dance programme Bellylatinofit, based on steps from popular latin and oriental dance, was designed. The effectiveness and health beneficial potential of the programme was tested together with nutritionally balanced diet and cereal fibre drink consumption in a 4 month long intervention study. The study group was created from women in the age 19-34 years, healthy, non smokers with body fat percentage above 29%. They were assigned into 3 intervention groups: Bellylatinofit, Bellylatinofit + Diet, Diet and a Control group. Bellylatinofit, a moderate intensity dance exercise, was attended three times a week (75 min. lessons). After 4 month of dance intervention, a trend in improvement of lipid parameters such as total and LDL cholesterol decrease was seen, although it was not statistically significant compared to a control group. A significant decrease was seen in the total weight, WHR and BMI index (p<0.05). Moreover, the incorporation of nutritionally balanced diet and cereal fibre drink consumption had a synergic effect on most evaluated parameters, including total and visceral fat mass loss and atherogenic index decrease (p<0.01). Acknowledgement: The work was supported by The Agency of the Ministry of Education, Science, Research and Sport of the SR for the Structural Funds in the frame of the Project ITMS 26240220040, by the APVV under the contract No. VMS P-II -0024-09 and by the young STU researchers grant No. 1324. Authors would like to thank Essentia, Ltd. Company for producing Actiglucane fibre drink and Mgr. Martin Križan, PhD. for his help with EUROFIT tests.